2000
DOI: 10.1034/j.1399-3003.2000.16d14.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function in patients with obstructivesleep apnoea syndrome

Abstract: Patients with obstructive sleep apnoea syndrome (OSAS) are subject to an increased cardiovascular morbidity including myocardial infarction and stroke. Platelets play an important role in the pathogenesis and triggering of acute cardiovascular syndromes. So far, the influence of OSAS on platelet function is not fully understood. Platelet aggregability to epinephrine, collagen, arachidonic acid, and adenosine diphosphate in vitro was measured in 17 consecutive male patients (53.0±2.1 yrs) with polysomnographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
1
13

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(129 citation statements)
references
References 28 publications
2
111
1
13
Order By: Relevance
“…There are several reports assessing the platelet activation status in patients with OSA 9) ; however, platelet aggregability is a more direct way of investigating platelet aggregation. There have been only two small-scale studies on platelet aggregability including 32 or 23 OSA patients, respectively, and these studies reported that the maximal aggregation rates of platelets at baseline between the OSA and control groups exhibited no differences 10,11) . Here, we systematically analyzed platelet aggregability by the optical aggregometer method in 124 OSA-suspected subjects at baseline and in 23 nCPAP-treated patients among them until 90 days.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports assessing the platelet activation status in patients with OSA 9) ; however, platelet aggregability is a more direct way of investigating platelet aggregation. There have been only two small-scale studies on platelet aggregability including 32 or 23 OSA patients, respectively, and these studies reported that the maximal aggregation rates of platelets at baseline between the OSA and control groups exhibited no differences 10,11) . Here, we systematically analyzed platelet aggregability by the optical aggregometer method in 124 OSA-suspected subjects at baseline and in 23 nCPAP-treated patients among them until 90 days.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] SDB was related with heart strain due to apnea and various cardiovascular diseases. Some studies have reported a relationship between SDB and myocardial ischemia, 2,[13][14][15] arrhythmia, [16][17][18] sudden death, 19) platelet coagulation, 20) and inflammatory cytokines, 21,22) all of which may trigger heart failure. These factors could therefore possibly cause heart failure between midnight and dawn.…”
Section: Discussionmentioning
confidence: 99%
“…De plus, il apparaît que le SAS accroît la coagulabilité du sang. En effet, les catécholamines sont augmentées chez les patients avec SAS et peuvent activer les plaquettes, ce qui augmente le risque de formation de caillots sanguins (Eisensehr et al, 1998;Sanner et al, 2000). Les patients avec AVC et SAS ont un taux sanguin de fibrinogènes plus élevé que les patients avec AVC sans SAS, ce qui contribue également à l'hypercoagulabilité du sang.…”
Section: Mécanismes D'apparition Des a Vc Et Des Ict Chez Les Personnunclassified
“…Une corrélation positive a été trouvée entre le taux de fibrinogène et la sévérité du SAS (Wessendorf et al, 2000b). Le traitement par CPAP permet de normaliser l'activation plaquettaire et le taux sanguin de fibrinogène (Sanner et al, 2000;Wessendorf et al, 2000b). …”
Section: Mécanismes D'apparition Des a Vc Et Des Ict Chez Les Personnunclassified